Promoter- and RNA polymerase II–dependent hsp-16 gene association with nuclear pores in Caenorhabditis elegans - Rohner, Sabine (The Rockefeller University Press, 2013)
Some inducible yeast genes relocate to nuclear pores upon activation, but the general relevance of this phenomenon has remained largely unexplored. Here we show that the bidirectional hsp-16.2/41 promoter interacts with the nuclear pore complex upon activation by heat shock in the nematode Caenorhabditis elegans. Direct pore association was confirmed by both super-resolution microscopy and chromatin immunoprecipitation. The hsp-16.2 promoter was sufficient to mediate perinuclear positioning under basal level conditions of expression, both in integrated transgenes carrying from 1 to 74 copies of the promoter and in a single-copy genomic insertion. Perinuclear localization of the uninduced gene depended on promoter elements essential for induction and required the heat-shock transcription factor HSF-1, RNA polymerase II, and ENY-2, a factor that binds both SAGA and the THO/TREX mRNA export complex. After induction, colocalization with nuclear pores increased significantly at the promoter and along the coding sequence, dependent on the same promoter-associated factors, including active RNA polymerase II, and correlated with nascent transcripts.